iPhone & iPad game development for dummies - Goldstein, Neal [ (Neal D.)]; Buttfield-Addison, Paris; Manning, Jon (For dummies, 2010)
Got an idea for a fun iPad or iPhone game but don't know what to do with it? Learn what's involved in becoming a registered developer, how to work with the SDK, key features of game architecture, how to market your games, and more